GAMBARAN POLA PEMBERIAN ASI DAN MP-ASI, PENYAKIT INFEKSI SERTA STATUS GIZI ANAK USIA 6-24 BULAN DI WILAYAH KERJA PUSKESMAS PERAWATAN LAWE PERBUNGA, ACEH TENGGARA - Dian Maulidta; Jumirah .; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Nutrition is a very important need in the process of growth and development of children, especially in the first two years of life. Breast milk feeding patterns and complementary foodsof not exactly can open the gates for various types of diseases and cause nutritional problems in children. The purpose of this study was to know the breast feeding patterns and complementary foods, infectious diseases and nutritional status of children ages 6-24 months in the Working Area of Community Health Center Lawe Perbunga, South East Aceh.This researchwas descriptive research with cross sectional approach. A sample of 77 children ages 6-24 months were measured in simple random sampling. Method of data collection by passing interview used questionnaire and measured child nutritional status based on index of weight for age (W/A), length for age (L/A) and weight for length (W/L). The results of the study showed that thebreast milkfeedingpatternof 29,9% good categories and 70,1%categories was not good. Complementary foods of 29,9% good categories and 70,1%categories was not good. The children ages 6-24 months with an infectioun diseases of 50,6% and no pain of 49,4%.Nutritional status based on the index W/A of 81,8%good nutrition categories, 16,9% of malnutrition categories and 1,3% of more nutrition categories. Nutritional status based on the index L/A of 49,4%of normal categories, 26.0% very short categories, 23,4% of short categories and 1,3% of high categories. While the nutritional status based on the W/L of 67,5% normal categories, 1,3% of very thin categories, 3,9% of thin categories and 27,3% of fat categories.Thus the need for counseling of the mother about the breast milk feeding patterns and complementary foods in children. Especially on exclusive breastfeeding, when children can be given complementary foods, and how the correct complementary foods includes types and forms complementary foods tailored to the development of the childs age. Keywords : Breast Milk Feeding Pattern, Complementary Foods, Infectious Diseases, Nutrition Status, Children Ages 6-24 Months